THE STUDY OF GENDER INEQUALITY FOUND IN DEBORAH ELLIS’S NOVEL “THE BREADWINNER” - Santi Prastyowati (Jurnal Perempuan dan Anak, 2019)
Inequality is clearly an important issue that requires much more attention in the world. Inequality practices in the community still trapped in the old paradigm such as treat someone by their race, culture, religion, and gender. However, is not easy to eliminate an inequality in the soceity. The current study analyze the topic namely gender inequality that happened to the main character’s life in “The Breadwinner” novel by Deborah Ellis. This study aimed to analyse the kind of inequality and the effect of it on main character’s life, the writer used qualitative descriptive method. Moreover, Parvana as a main character was selected based on her experience in gender inequality. In addition, Longwe’s women empowerment framework was used to prove that there are gender inequality happen in the story of the novel. The result showed that gender inequality positively occurs in the life of the main character because the story of the novel does not fullfil the five levels of equality (welfare, access, conscientisation, participation, and control) that Longwe describes in her women empowerment framework. Moreover, the lack of equality that happend in the story has resulted in several negative effects such as poverty, lack of choice, absence of security, discrimination, and power abuse.